Highly selective retrieval of accurate DNA utilizing a pool of in situ-replicated DNA from multiple next-generation sequencing platforms. Issue 7 (18th January 2018) - Lim, Hyeonseob; Cho, Namjin; Ahn, Jinwoo; Park, Sangun; Jang, Hoon; Kim, Hwangbeom; Han, Hyojun; Lee, Ji Hyun; Bang, Duhee
Abstract: Scalable and cost-effective production of error-free DNA is critical to meet the increased demand for such DNA in the field of biological science. Methods based on 'Dial-out PCR' have enabled the high-throughput error-free DNA synthesis from a microarray-synthesized DNA pool by labeling with retrieval PCR tags, and retrieving error-free DNA of which the sequence is identified via next generation sequencing (NGS). However, most of the retrieved products contain byproducts due to background amplification of redundantly labeled DNAs. Here, we present a highly selective retrieval method of desired DNA from a pool of millions of DNA clones from NGS platforms. Our strategy is based on replicating entire sequence-verified DNA molecules from NGS plates to obtain population-controlled DNA pool. Using the NGS-replica pool, we could perform improved and selective retrieval of desired DNA from the replicated DNA pool compared to other dial-out PCR based methods. To evaluate the method, we tested this strategy by using 454, Illumina, and Ion Torrent platforms for producing NGS-replica pool. As a result, we observed a highly selective retrieval yield of over 95%. We anticipate that applications based on this method will enable the preparation of high-fidelity sequenced DNA from heterogeneous collections of DNA molecules.